Multimorbidity and healthcare utilization among Black Americans: A cross‐sectional study - Sangwoo Ahn; Marissa Bartmess; Lisa C. Lindley (Wiley, 2022)
Abstract Aim Racial disparities between multimorbidity presence and healthcare utilization are present within the United States, but less is known about the relationship between multimorbidity presence and healthcare utilization among Black Americans. This study was conducted to examine the relationship between multimorbidity and healthcare utilization among Black Americans. Design Cross‐sectional study. Methods This study (n = 425, 57% female) used adult level data from the 2012-2013 Connecticut Health Care Survey. Results Multivariate logistic regressions indicated that multimorbidity presence predicted a doctor and a specialist visit, but not a dentist visit. Conclusion This study identified multimorbidity presence as a predictor for healthcare utilization, but further research is necessary to understand healthcare utilization experiences among Black Americans with multimorbidity to assess the quality of care. Appropriate measures should also be considered to increase access to dental care for Black Americans with multimorbidity.